Assessing the Relationship Between Public Acceptance and Access to Primary Health Services - Ferry Fadzlul Rahman (GLOBAL HEALTH SCIENCE GROUP, 2026)
Primary healthcare serves as the foundation of an effective health system, and its utilization is strongly influenced not only by service availability but also by community acceptance. In urban areas with an increasing number of primary healthcare facilities, understanding how public acceptance affects access to services is essential for improving service utilization and equity.This study aims to determine the relationship between public acceptance with access to service health primary in Clinic Mitra Gustiana, Samarinda City. This research is a quantitative research with approach cross-sectional. Sample in study This as much as Ninety-six respondents were selected using stratified random sampling. Data were collected through a closed-ended questionnaire that had been tested for validity and reliability. Data analysis was performed using the Spearman Rank test to determine the relationship between the two variables. variables. Results research obtained p-value = 0.001 (p < 0.05) Which show existence connection Which A significant correlation was found between community acceptance and access to primary healthcare services. The Spearman correlation coefficient showed a value of 0.340, indicating a positive correlation with moderate strength. The results of this study are expected to serve as evaluation material for primary healthcare providers, particularly the Mitra Gustiana Clinic, in improving service quality based on community acceptance to expand access to services equitably and sustainably.